Strengthening Family Bonds and Promoting Rural Development: The Impact of Universal Social Pensions in Tanzania - Wagana, Paskas (Baileo: Jurnal Sosial Humaniora, 2024)
This article examines the impact of universal social pensions on strengthening family bonds and promoting rural development in Tanzania, a country experiencing rapid demographic shifts and an aging rural population. The study aims to assess how cash transfers to the elderly contribute to intergenerational solidarity and socio-economic advancement in rural communities. Using data from a 2012 cross-sectional survey involving over 900 elderly participants in the Mwanza region and complementary findings from the 2019 SAUT Survey across three regions—Arusha, Mtwara, and Mwanza—this research applies a mixed-methods approach to explore the multidimensional effects of social pensions. The findings reveal that universal social pensions play a vital role in reducing poverty, improving health and nutrition, and stimulating local economic activities such as agriculture and rural markets. Moreover, pensions serve as a crucial support mechanism that reinforces familial responsibility and intergenerational care. However, the study also identifies emerging challenges, including weakened traditional family structures, resource limitations, and shifting socio-cultural dynamics that marginalize older adults. The novelty of this research lies in its integration of family sociology and rural development perspectives, positioning universal social pensions not merely as welfare tools but as catalysts for social cohesion and rural resilience. This study contributes to social sciences and humanities by offering policy recommendations for inclusive and sustainable aging strategies in rural contexts.